Gedichte - Archilochos (Sammlung Tusculum, 2014)
Frontmatter -- INHALT -- 1-17. ELEGI -- 18-87. TRIMETRI -- 88-167. TETRAMETRI -- 168-204. ΕPODI -- 205-95.INCERTI GENERIS -- 296-321. DUBIA -- 322-33. SPURIA -- ANHANG -- ANMERKUNGEN -- EINFÜHRUNG -- ZU TEXT UND ÜBERSETZUNG -- LITERATURHINWEISE